Principais barreiras para a implementação da manufatura aditiva no Brasil - Almeida, Alberto Mendonça de (2020)
Additive manufacturing (MA) had a huge development since the 1980s. This is considered a modern and disruptive technology of manufacturing technique, which is perfectly adapted to the innovative and new concept of the growing 4.0 industry, which are employing methods of adding material, instead of traditional method that consists of removing material out of a metal parte. All this modernity brings substantial benefits such as economic, financial and environmental. However, the literature review demonstrates that the adoption of this technology has found several barriers where they were implemented. Generically, these barriers were related to energy, materials, labor, machinery, regulation and manufacturing processes. Brazil could not be out of this revolutionary new technological process, neither avoid going through the same difficulties identified in other locations. Therefore, this study aimed to do the exploratory bibliographic survey of barriers for adopting additive manufacturing found in the literature and then, through a case study, identify which are the main barriers and challenges for the implementation of MA technology in Brazil. The results found will fill a gap in the literature because no studies were made before about this subject in Brazil. This will work as a guide for industry to be able to make appropriate preparation for this huge challenge that inevitably is coming soon for Brazil.